DESIGNING A MODEL FOR THE IMPROVEMENT OF ORGANIZATION’S SOCIAL RESPONSIBILITY PERFORMANCE BASED ON PRINCIPLES, POLICIES AND PROGRAMS OF SOCIAL RESPONSIBILITY AT THE MINISTRY OF ECONOMIC AFFAIRS AND FINANCE AND THE SUBSIDIARY COMPANIES - Nasiri, Hossein; Pourkiani, Masoud; Sayadi, Saeed (Revista Inclusiones, 2019)
The purpose of this research is designing a model for the improvement of Organization’s social responsibility performance based on principles, policies and programs of social responsibility at the Ministry of Economic Affairs and Finance and subsidiary companies. The research community consisted of two groups: the first group includes the experts. By experts we mean all the experts that have acquaintance with the corporate social responsibility and their number is unspecified; 30 individuals were selected as experts from among them; and the second group includes all the managers and professionals of upper organizational rank at the Ministry of Economic Affairs and Finance and its subsidiaries in the country which were 7789 people distributed in 31 provinces. The sample size was 400 people that were selected according to Cochran formula. In the second group, the sampling method was random, stratified, and fits the size of the society. The research method was descriptive-survey and to analyze the data statistical methods were carried out at two levels of descriptive and inferential tests, using SPSS20, and Amoos8/8. Considering the mean of the variables in the research, it can be said that these variables are above the satisfactory level. The results indicate that there is a relationship between policies with social responsibility programs, and the principles of social responsibility, and between accountability, transparency, ethical behavior, respect for the stakeholders’ interest, respect for international norms of behavior, respect for the law, and respect for human rights with the corporate social responsibility at the Ministry of Economic Affairs and Finance and the subsidiary companies.